Statistical analysis and conformity testing of concrete in port construction work - Larrossa,M. C. (2014)
Conformity control of concrete is part of a range of control and standard methods which must be employed in all construction work to assure its compliance with quality requirements. The compressive strength of the concrete is considered as a random variable that must be controlled by standardized sampling and testing in order to ensure the structural safety. Therefore, the use of a large amount of compressive strength test results of concretes with similar characteristics has been seen as an important tool in the assessment of current standard norms. This paper describes an analysis based on the conformity control used in large port construction works which have recently been carried out in the Rio Grande Port, located in Rio Grande, RS, Brazil. Statistical analyses were performed and acceptance tests of the product were conducted. They were based on the acceptance criteria of different methodologies from different continents and showed the variations that can occur in the results of the conformity testing, depending on the adopted model. It is worth mentioning that the concrete used in port construction works in the region has been in accordance with current Brazilian norms.